2018
DOI: 10.1016/j.surfcoat.2018.01.078
|View full text |Cite
|
Sign up to set email alerts
|

Properties of HVOF-sprayed Stellite-6 coatings

Abstract: Stellite-6 coatings were deposited onto AISI 304 stainless steel substrate by gas-fueled HVOF spraying, systematically varying the process parameter settings. By operating the HVOF torch with a fuel-rich mixture, dense coatings (<1% porosity) are produced, containing up to ≈3 vol.% oxide inclusions. A substantial amount of a Cr-rich f.c.c. phase is found, mainly produced by quenching of molten lamellae, and distinct from the equilibrium, Co-based f.c.c. solid solution retained in unmelted particles. These coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…Zhu et al [41] reported a decrease of wear rate of undoped Fe-40Al with increasing temperature up to °C. Other authors have reported that more rapid oxidation at 800 °C than at 400 °C may stabilize the adhesion of the oxide layer reducing friction [42]. °C.…”
Section: Coatings Performancementioning
confidence: 93%
“…Zhu et al [41] reported a decrease of wear rate of undoped Fe-40Al with increasing temperature up to °C. Other authors have reported that more rapid oxidation at 800 °C than at 400 °C may stabilize the adhesion of the oxide layer reducing friction [42]. °C.…”
Section: Coatings Performancementioning
confidence: 93%
“…The obtained hardness value of cobalt-based alloy coating was 553 HV 0.3 , which was attributed to the coating with the dense structure and the Co-based fcc-phase, as shown in Figure 8. The Cr-rich M 7 C 3 phase was visible in the coating XRD patterns [19,20]. The hardness of the WC-12Co and WC-17Co coatings were found to be higher than that of the cobalt-based alloy coating, which was due to the distribution of the WC particles in the matrix friction that acted as a hardness reinforcement [21][22][23][24].…”
Section: Discussionmentioning
confidence: 97%
“…Wear-resistant Stellite coatings are applied by various methods such as thermal spraying [9], gas tungsten arc welding (GTAW) [10], plasma transferred arc (PTA) [11], flame spraying [12], and laser metal deposition (LMD) [13]. LMD is a laser cladding approach which can be used to fabricate functional, three-dimensional components.…”
Section: Introductionmentioning
confidence: 99%